Preventing violence and harassment in employment relationships - Stanytė, Karolina; Latakaitė, Greta (Vilnius University Open Series, 2024)
This article analyses issues related to violence and harassment in employment relationships. This topic is widely addressed internationally, but in the national context the issue of violence and harassment in employment relations has not been fully and thoroughly analysed, although it is of great importance for society. Individuals exposed to violence and harassment can suffer not only physical but also emotional experiences and, as a result, long-term negative consequences. In this context, appropriate legislative regulations are important and the 2022 amendments to the Labour Code of the Republic of Lithuania are therefore of particular relevance and are examined in this paper. The development of appropriate preventive measures is a particularly relevant aspect, which is why this paper delves into the development of effective preventive measures in the workplace that can help to ensure the effective protection of workers. The article also contains analysis of the mechanism for redressing workers’ rights.
Keywords: violence and harassment; employment relationship; employee; employer; mobbing; Labour Code of the Republic of Lithuania; International Labour Organisation